Efeito da radiação gama sobre a redução de microrganismos patogênicos, a estabilidade dos lipídios e as características sensoriais em caudas de camarões congelados - Abreu, Virgínia Kelly Gonçalves (2006)
Irradiation represents an efficient technique to extend shelf life of several foods and the interest in using this technology has been growing in the last years because besides improving food safety it produces minimal alterations in the food constituents. Thus, this study investigated the effect of ionizing irradiation (60Co) of frozen and packaged shrimp on microorganisms as well as on some chemical and sensory characteristics of the product. Cultivated shrimp (Penaeus vannamei) from local farms processed into shrimp tails were packaged, frozen, irradiated and analyzed. The study was divided in two stages. The first stage was intended to verify the effect of the gamma radiation on the population of inoculated Vibrio cholerae O1 and Salmonella enteritidis bacteria. It used a complete randomized factorial (4 x 3) design with four irradiation doses (0, 2, 4 and 6kGy) and three inoculation modalities (one with V. cholerae O1, one with S. enteritidis and one without microorganisms). The second stage aiming to verify the effect of the gamma irradiation on the chemical stability of lipids, color and instrumental texture of shrimp followed a complete randomized factorial (4 x 5) design with four irradiation doses (0, 2, 4, and 6kGy) and five replicates. Sensorial analysis followed a complete randomized factorial of balanced complete blocks, where the panelist was considered as block. The experimental units (UE) from the first stage were analyzed for V. cholerae O1 and S. enteritidis survival after the irradiation procedure, while those from the second stage were analyzed for thiobarbituric acid reactive substances (TBARS), instrumental color and texture and sensory evaluation of the meat. As irradiating dose increased a significant (p<0.05) reduction in V. cholerae O1 and S. enteritidis counts was observed. TBARS values decreased (p<0.05) in shrimp irradiated with 6kGy related to those in non irradiated shrimp. Also, color component L* increased (p<0.05) in shrimp irradiated with 6kGy dose as compared to that irradiated with the 2kGy dose. No effect of irradiation was found on color components a* and b* or on instrumental texture values. Sensory global acceptance presented a significant reduction (p <0.05) with the dose of 6kGy as related to the doses of 2kGy or 0kGy. However, color acceptance and texture and the intensity of the attributes aroma, flavor and juiciness were not affected (p>0.05). Therefore, irradiation treatment in doses up to 6kGy on frozen and packaged shrimp tails significantly reduces V. cholerae O1 and S. enteritidis counts with minor effects on sensory characteristics in cooked shrimp.